Small uncountable powers of the Sorgenfrey line may not be weakly pseudocompact - Rojas-Hernández, Reynaldo (Topology Proceedings, 2024)
It is established that if Martin's Axiom $M A(κ)$ holds for some cardinal $κ$, then the $κ$-power $\mathbb{S}^κ$, of the Sorgenfrey line $\mathbb{S}$, is not weakly pseudocompact.